VD_FINDINFO Jug / 2014 / 304 vom 18. März 2014 - VD Tribunal cantonal (2014)
BRIGANDAGE, PRÉSOMPTION D'INNOCENCE, CONSTATATION DES FAITS, FIXATION DE LA PEINE, PEINE COMPLÉMENTAIRE | 140 CP, 47 CP, 49 al. 2 CP